Grumplets and pests - Citro, Asia (Citro, Asia. Zoey and Sassafras, 2019)
In the seventh book, Zoey and Sassafras are excited to enjoy their summer with their magical friends. But . . . why is everyone so grumpy? A bunch of bad days one after the other lead Zoey to suspect that something more is afoot. It's up to Zoey and Sassafras to solve the mystery before they end up with one bummer of a summer!